COMPARISON BETWEEN SPORT PARTICIPATION MOTIVATION AND GOAL-ORIENTATION OF YOUTH ATHLETES: THE ROLE OF PARENTS' EDUCATION LEVEL - Noshin Benar; Mohsen Loghmani (Kharkov National Pedagogical University, 2012)
The aims of present study was to (A) compare and prioritizing the main six motivations of sport participation of youth athletes, (B) compare and prioritize task and ego-orientation of youth athletes, and (C) the role of parents' education level and its impact on the motivation of sport participation and goal-orientation youth athletes. In the study, descriptive-analytic design was applied. For the study 376 Iranian youth athletes were singled out by cluster-random sampling. They answered to participation motivation questionnaire (PMQ) and task & ego-orientation in sport questionnaire (T.E.O.S.Q). Also data about parents' education level (PEL) was obtained using questions about demographic features. The findings showed that those who participated in individual sports had more motivation for status than team sports athletes and they were more ego-orientation. Also it was found that more highly educated mothers came to induce internal motivation in youth athletes using Kruskal-Wallis test, whereas more highly educated fathers came to induce both internal and external motivation to them. It seems that those athletes who participated in individual and open-skilled sports are more ego-oriented than those who participated in team and open-skilled sports. The feedbacks which are based on task orientation are probably provided, along with promotion of mothers' education level; however with promotion of fathers' education level, both of these feedbacks and those based on ego-orientation will be provided, probably for their children to participation in sport activities.